2018
DOI: 10.1103/physrevb.98.115305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chaos on two-dimensional spin transport

Abstract: The role of classical dynamics in spin transport is an intriguing problem from the point of view of classical-quantum correspondence, as spin is a purely relativistic quantum mechanical variable with no classical counterpart. Nevertheless, due to spin-orbit coupling (generally referred to as the relativistic interaction of a particle's spin with its motion inside a potential) and because the orbital motion does have a classical correspondence, the nature of the classical dynamics can affect spin. A basic trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…20. The idea originates from recent studies to control spin polarization by exploiting classical chaotic dynamics 238,239 and spin Fano resonances. 240 The role of classical dynamics in spin transport is intriguing from the point of view of a classical-quantum correspondence, as spin is a purely relativistic quantum mechanical variable without a classical counterpart.…”
Section: Controlling Spin Polarization and Entanglement In A Hybrid C...mentioning
confidence: 99%
See 4 more Smart Citations
“…20. The idea originates from recent studies to control spin polarization by exploiting classical chaotic dynamics 238,239 and spin Fano resonances. 240 The role of classical dynamics in spin transport is intriguing from the point of view of a classical-quantum correspondence, as spin is a purely relativistic quantum mechanical variable without a classical counterpart.…”
Section: Controlling Spin Polarization and Entanglement In A Hybrid C...mentioning
confidence: 99%
“…Of particular interest is the spin degree of freedom in the weak SO coupling regime where, as existing studies suggested, it is possible to use classical chaos to enhance SO entanglement significantly at the expense of spin coherence. [238][239][240]…”
Section: Decoherence and Entanglement Considerationsmentioning
confidence: 99%
See 3 more Smart Citations